2003
DOI: 10.1104/pp.102.011122
|View full text |Cite
|
Sign up to set email alerts
|

TheMedicagoSpecies A2-Type Cyclin Is Auxin Regulated and Involved in Meristem Formation But Dispensable for Endoreduplication-Associated Developmental Programs

Abstract: (M.L., P.L., P.A.)Phytohormones as well as temporal and spatial regulation of the cell cycle play a key role in plant development. Here, we investigated the function and regulation of an alfalfa (Medicago sativa) A2-type cyclin in three distinct root developmental programs: in primary and secondary root development, nodule development, and nematode-elicited gall formation. Using transgenic plants carrying the Medsa;cycA2;2 promoter-␤-glucuronidase gene fusion, in combination with other techniques, cycA2;2 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 56 publications
2
60
0
4
Order By: Relevance
“…As nodules are formed on roots it has been hypothesized that the nodule developmental program is derived from the lateral root developmental program (Nutman, 1948;Hirsch et al, 1997;Mathesius et al, 2000;de Billy et al, 2001;Roudier et al, 2003;Bright et al, 2005;Desbrosses and Stougaard, 2011). Recently, the expression of several root meristem regulators has been observed in the nodule meristem (NM) (Osipova et al, 2011(Osipova et al, , 2012Roux et al, 2014), thereby providing molecular support for this hypothesis.…”
Section: Introductionmentioning
confidence: 76%
“…As nodules are formed on roots it has been hypothesized that the nodule developmental program is derived from the lateral root developmental program (Nutman, 1948;Hirsch et al, 1997;Mathesius et al, 2000;de Billy et al, 2001;Roudier et al, 2003;Bright et al, 2005;Desbrosses and Stougaard, 2011). Recently, the expression of several root meristem regulators has been observed in the nodule meristem (NM) (Osipova et al, 2011(Osipova et al, , 2012Roux et al, 2014), thereby providing molecular support for this hypothesis.…”
Section: Introductionmentioning
confidence: 76%
“…Xylem pole pericycle cells, from which founder cells are recruited, carry cytological features such as dense cytoplasm, large nuclei, and small vacuoles typical of meristematic cells (13). In addition, it has been shown that these cells are capable of fast entry into the cell cycle because of sustained expression of cell cycle genes such as CDKA;1 or CycA2;1 (14,15). However, only very few cells of the pericycle tissue layer are recruited to become founder cells, and until now no founder cell-specific marker or mutants affected specifically in founder cell specification have been found (14).…”
mentioning
confidence: 99%
“…However, there is direct evidence that auxin also regulates the expression of some regulatory subunits. Thus, alfalfa CYCA2;2 expression is induced by auxin and during lateral root initiation and elongation (Roudier, et al, 2003). Consistent with such expression pattern, CYCA2 has been involved in mitotic cycles but not in endocycles and cell differentiation.…”
Section: Auxinmentioning
confidence: 57%